The effect of climate change to the population of rhinoceros beetle (Oryctes rhinoceros) at selected oil palm plantation / Nor Narisa Edora Sabidin - Sabidin, Nor Narisa Edora (Faculty of Plantation and Agrotechnology, 2018)
Rhinoceros beetle (Oryctes rhinoceros) is one of the insect pest that limits the production and sustainability of oil palm crop. The objective of this study is to determine the distribution and abundance of rhinoceros beetle over climate change at selected oil palm plantation and to evaluate the correlation between populations of rhinoceros beetle and climatic factors especially rainfall and temperature. As known, Malaysia is one of the countries that have many climate changes problem. In this study, the pheromone trap was setting systematically and pheromone (ethyl-4-methylloctanoate) has been used as lures to attract the beetle. The result show that there are negative correlation between rainfall and rhinoceros beetle population where the increasing amount of rainfall decrease the population of rhinoceros beetle (Pearson correlation –0.047, P-value 0.667). There also negative correlation between temperature and populations of rhinoceros beetle population where the increasing amount of temperature decrease the population of rhinoceros beetle (Pearson correlation –0.033, P-value 0.758). This study shown that rainfall and temperature factor not influences the population of rhinoceros beetle.